Registration System for the Faculty of Science - Sana'a University - Al-Sharafi, Ali Mohammed (2001)
The purpose of this project is to develop a computerized registration system for Faculty of Science in Sana' a University - Yemen, since the registration system in the faculty still manual. This system was developed using Oracle as a DBMS, because of the facilities it provides such as, unlimited database and high-speed data access. The waterfall model was the model that has been chosen to develop this system because it does not require a user feedback like prototyping model or some other models and this is because this project has been developed in a different place (i.e. not in the same country of the Sana'a University). With this system, the registration process can be easily done accurately, faster, and with more security than the manual process.